The impact of thienothiophene isomeric structures on the optoelectronic properties and photovoltaic performance in quinoxaline based donor-acceptor copolymers - Singh, Ranbir R.; Pagona, Georgia; Gregoriou, Vasilis G.; Tagmatarchis, Nikos; Toliopoulos, Dimosthenis; Han, Yang; Fei, Zhuping; Katsouras, Athanasios; Avgeropoulos, Apostolos; Anthopoulos, Thomas D.; Heeney, Martin; Keivanidis, Panagiotis E.; et al. (My University, 2015)
The influence of the monomer's isomeric structure on the optical, electrochemical, charge transporting properties and photovoltaic performance of donor-acceptor (D-A) conjugated polymers has been demonstrated for the first time by studying two D-A copolymers consisting of bis(3-octyloxy)phenyl)quinoxaline as the electron deficient unit and the two isomeric structures of thienothiophene (thieno[3,2-b]thiophene and thieno[2,3-b]thiophene) as the electron rich units. The drastic effect of incorporating two different isomeric structures on the polymer backbone of these copolymers, manifests in changes observed in their optical, electrochemical and charge transporting properties. In contrast, the overall photovoltaic performance of the copolymers is similar, but distinct differences in the device photocurrents occur. These differences were attributed to morphology variations rather than the balanced mobility ratio. For further developments in the field, the isomeric structures of different functional monomers should be considered in the designing of new materials with even superior performance.
Keywords: Heterojunction solar-cells; Band-gap copolymers; Conjugated polymers; Charge-transport; Semiconducting polymers; Organic electronics